2015
DOI: 10.1177/0022042615589404
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Alcohol Use Patterns From 25 European Countries

Abstract: This study's purpose is to describe European adolescents' alcohol use patterns by grouping adolescents regarding their current alcohol use by cluster analysis (CA). Discriminant and latent profile analyses (LPA) evaluate and validate the solution that will be described further by ANOVAs. From 25 European countries, 57,771 students (49.4% male, 13.87 years) are grouped using hierarchical and k-means clustering. Alcohol use is measured by frequency of drinking occasions during the previous month and number of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Adolescent drinking frequently consists of heavy binges separated by periods of abstinence, often clustering around social events (Bräker, Göbel, Scheithauer, & Soellner, 2015). Binge drinking is defined as a pattern of alcohol use that brings blood alcohol concentration (BAC) levels to 0.08 g/dL, which typically occurs after the consumption of four or more standard alcoholic drinks for females and five or more drinks for males, over a 2 h period (Substance Abuse and Mental Health Services Administration, 2016; National Institute on Alcohol Abuse and Alcoholism, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent drinking frequently consists of heavy binges separated by periods of abstinence, often clustering around social events (Bräker, Göbel, Scheithauer, & Soellner, 2015). Binge drinking is defined as a pattern of alcohol use that brings blood alcohol concentration (BAC) levels to 0.08 g/dL, which typically occurs after the consumption of four or more standard alcoholic drinks for females and five or more drinks for males, over a 2 h period (Substance Abuse and Mental Health Services Administration, 2016; National Institute on Alcohol Abuse and Alcoholism, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of empirical studies examined the relationship between general self-control and adolescent alcohol use and revealed that high general self-control is an important protective factor for several alcohol-related outcomes [8,18,[20][21][22][23][24][25][26][27][28][29][30][31]. Longitudinal studies have demonstrated the effects of general self-control on adolescents' alcohol use.…”
Section: General Self-control and Adolescent Alcohol Usementioning
confidence: 99%
“…However, young drinkers are not a homogenous group and the concept of "binge drinking" overlooks the complexity and heterogeneity of their alcohol use. Indeed, many scholars have called for a move away from broad classifications such as "binge drinkers" (White, 1987;Carey, 2001;Gmel, Klingemann, Muller, & Brenner, 2001) and single indicator measurement of problematic alcohol use (Rehm et al, 2004;Reboussin, Song, Shresha, Lohman, & Wolfson, 2006;Bräker, Göbel, Scheithauer, & Soellner, 2015), as these can mask distinct types of drinkers and potentially differential risks of harm.…”
Section: Introductionmentioning
confidence: 99%
“…LCA categorizes individuals, not based on theoretical assumptions, but rather explores patterns of drinking-related indicators empirically to examine the underlying structure among cases (i.e., latent taxonomic structure) (Uebersax, 2009). Thus, when considering recreational drinking practices, resulting groups can thus be characterized as expressive and distinctive drinking behavioral profiles (Bräker et al, 2015). Three studies have used DSM criteria to classify alcohol users and found between three and four classes that are broadly similar across different geographical contexts (McBride, Teesson, Baillie, & Slade, 2011;Casey, Adamson, & Stringer, 2013;Castaldelli-Maia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation